2014
DOI: 10.1007/s00403-014-1519-x
|View full text |Cite
|
Sign up to set email alerts
|

The interleukin-6 and interleukin-1A gene promoter polymorphism is associated with the pathogenesis of acne vulgaris

Abstract: Acne vulgaris is a skin disorder with a complex pathogenesis. Better treatment strategies require comprehensive knowledge of molecular factors contributing to the acne pathophysiology. Recent studies are focused on investigating the influence of inflammatory cytokines on the disease. This case-control study investigated the association of IL-6-572 G/C and IL-1A-889 C/T gene polymorphisms with acne in a Pakistani population. Pakistani subjects (380 healthy controls and 430 acne patients) were enrolled in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 31 publications
5
32
2
Order By: Relevance
“…A significant difference was observed in the distributions of IL‐1A genotypes (CC, CT, and TT) in AV patients and control subjects. This is in agreement with Sobjanek et al and Younis & Javed, who confirmed the same association in Pakistani and Polish populations, respectively. The T allele (mutant allele) at this position is associated with a fourfold increase in IL‐1A expression .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A significant difference was observed in the distributions of IL‐1A genotypes (CC, CT, and TT) in AV patients and control subjects. This is in agreement with Sobjanek et al and Younis & Javed, who confirmed the same association in Pakistani and Polish populations, respectively. The T allele (mutant allele) at this position is associated with a fourfold increase in IL‐1A expression .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the TT genotype of IL‐1A (−889C/T) polymorphism significantly increased the transcriptional activity of IL‐1A gene compared with the CC genotype . In fact, the frequency of T allele and TT genotype in acne vulgaris patients was higher than that in the control subjects group in our study and in the Sobjanek et al and Younis & Javed studies too. This suggests that the TT genotype in IL‐1A is linked with increased risk for developing acne vulgaris.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Elevated levels of pro-inflammatory IL1α have been detected in most open comedones of acne vulgaris2829. External treatment with the IL1α protein leads to hyperproliferation and abnormal differentiation in isolated pilosebaceous units in vitro 3031.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are relatively few studies on IL-6 gene polymorphism in acne patients. It has recently been reported that the IL-6 and IL-1α gene promoter polymorphisms are associated with the pathogenesis of acne vulgaris [35]. IL-1α has been widely studied in inflammation and is considered to affect the pathogenesis of acne [36]; it also contributes to paracrine signaling between keratinocytes and fibroblasts during wound healing.…”
Section: Discussionmentioning
confidence: 99%